Theoretical Consideration of Axial Ratio Deterioration in CP Loop-Shaped Antennas - Amit Mehta (IEEE Antennas and Wireless Propagation Letters, 2023)
Conventionally, the deterioration in the axial ratio (AR) for a circularly polarized antenna based on a traveling wave current is explained using backward currents reflected from the antenna arm end. This letter reveals the existence of a new cause for AR deterioration in a situation of no backward currents. For this, a theoretical loop antenna model of one-guided wavelength circumference is constructed, where only a forward traveling wave current (a positive s '-directed current) flows with attenuation due to the radiation. The derived AR equation finds that the AR deteriorates due to the attenuation of the current, even when backward currents do not exist. Subsequently, a current that flows in the direction normal to the positive s '-directed current (a t '-directed current specified by perturbation weight p ) is added to the loop. It is found that the AR in the presence of the attenuating current is improved by virtue of the positive t '-directed current.